In situ nanomechanical characterization of hydrogen effects on nickel-based alloy 725 under different metallurgical conditions. (1st February 2023) - Lu, Xu; Ma, Yan; Peng, Ding; Johnsen, Roy; Wang, Dong
Highlights: In-situ nanoindentation test was used to study the H effect on alloy 725. Both solution-annealed and precipitation-hardened alloy 725 were tested. H effect on surface integrity and nanomechanical properties were studied in detail. Different H behaviors were compared based on H content and microstructure. Abstract: The effect of hydrogen on the surface morphology and nanomechanical properties of Ni-based Alloy 725 under solution-annealed (SA) and precipitation-hardened (API) conditions was thoroughly studied. The investigation involved in situ nanoindentation testing, microscopy characterization, statistical analysis, and numerical simulation approaches. The results showed the distinctive effects of hydrogen on the pop-in and hardness in the SA and API samples. For the SA sample, hydrogen mainly dissolved as solid solute in the matrix, causing enhanced lattice friction on the dislocation motion and increasing the internal stress via lattice expansion. Thus, an enhanced hardness, a reduced pop-in width/load ratio, and numerous surface steps were detected in the presence of hydrogen. For the API sample, the strengthening γ′′ phases were the stress concentrators, and the dislocations nucleated heterogeneously, demonstrating indistinctive pop-in phenomena. Furthermore, the precipitates in the API sample affected the trapping behavior of hydrogen, thereby resulting in the hardness change, which reflected the competition between solution hardening in the matrix and vacancy softening mechanism in precipitates.